A curricularização das habilidades socioemocionais na educação infantil da região oeste do Paraná - Marçal, Cleonice (2024)
The thesis presents a qualitative and theoretical analysis on the teaching of socio-emotional skills in the National Common Curricular Base (BNCC) and in the Pedagogical Proposal of the Association of Municipalities of Western Paraná (PPC/AMOP). The general objective is to problematize the proposal for Early Childhood Education regarding the development of emotions and feelings. The reference for this investigation is in the comparison of the adequacy of the Curricular Pedagogical Proposal of Western Paraná (AMOP) with the BNCC regarding the introduction of socio-emotional skills in Early Childhood Education. From the dialectical method, the introduction of socio-emotional skills is analyzed in relation to the proposals of Brazilian educational public policies regarding the curriculum for Early Childhood Education, opposing materialistic and idealistic conceptions. It is concluded that teaching based on socio-emotional competencies is outlined in the BNCC as idealistic, for projecting a future society. For this reason, the possibility of a curriculum that fosters the development of emotions and feelings through materialist and dialectical conceptions is of significant importance because of the aspect that prioritizes human development, based on the material conditions found in reality. As for the curricular proposal of the West of Paraná (PPC/AMOP), it is evident that, although it encompasses the aspects of the conceptions of the Historical-Critical Theory and the Historical-Cultural Theory in its philosophical, pedagogical and psychological theoretical assumptions, in practice it evidences the idealistic and behavioral curriculum conceived in the Pedagogy of Competences, such as the BNCC.